Is Emotional Adjustment Status Predictor of the IUD Survival? - Ziba Farajzadegan; Ahmad Reza Zamani; Leila Manzouri; Parisa Mirmoghtadaee (Tehran University of Medical Sciences, 2009)
Objective: To evaluate the effect of emotional adjustment on IUD continuation to understand why persons with similar clinical problems have different interpretation and select different strategies to cope with their complaints. Materials and Methods: This historical cohort study was carried out on 12 randomly chosen health centers of Isfahan province in 2007. Two hundred forty eight literate and married women aged 15-49 years who had chosen IUD as a contraceptive method since 2002 entered the study. After explaining the aim of study and taking informed consent, women completed the demographic, individual characteristics and 32 questions in emotional domain of Bell's Adjustment Inventory (adult form). May 2007 was considered the end time of IUD consumption as a defined outcome. Data analysis was performed with the SPSS version 15. T-test, chi-square, Mann-Whitney, General Linear Model, Regression were used for data analysis. Results: During this period 60% (146) of women preserved their IUD and 40% (98) of them removed their IUD. The mean score of emotional adjustment was 16.16±6.28 in IUD preserved women in comparison to 18.23±5.63 in IUD removed women. Poor ,moderate and good  grades of emotional adjustment were 54%, 40% and 6% in IUD preserved woman vs 72.4% , 24.5% and 3.1% in IUD removed women. Conclusion: Psychological factors such as emotional adjustment can influence IUD survival; so improved counseling and good candidate selection before IUD insertion is recommended.